The Meaning of Tranquility in Contemporary Javanese Kawruh - Selamet, Moch.; Ishomuddin, Ishomuddin; Wahyudi, Wahyudi; Katonoi, Rinikso (Technium Social Sciences Journal, 2021)
The purpose of this research is to find out the contemporary Javanese in interpret and practice tentrem as a noble philosophy of ancestral heritage Javanese. They chose it to be a way of life in facing contemporary currents that are open society so that there was a process of cultural assimilation (hybrid culture). Thus the process, tinemune ngelmu kanthi laku, mawas diri, andmanunggale gusti kawulo. So that the Javanese achieve peace of mind are collectively guyub rukun and harmonious with the character of wah, weh, woh. This study uses a qualitative approach to the type of ethnographic research (strands of local culture). To collect data used interviews (jagongan) and observation. Research sampling using people who have networks, not those who join the sect (clans) but are independent individuals have no monitoring, tolerance, empathy for different views in determining behavior and practice, related to traditional philosophical values. While the data analysis technique is based on logic inductive, analysis moves from hieving something specific in the field to findings general, through data analysis on the basis of the theory used. The conclusions from this study are (1) contemporary Javanese people still preserving the teachings of Javanese philosophy consistently, despite lifestyle have experienced many changes, (2) the Javanese believe that the peace of mind in true happiness cannot be fully fulfilled only with matterial wealth (sakbutuhe), (3) the Javanese live in harmony not individual, (4) in peace in Javanese people prefer needs the piece of mind and soul. Keywords: “Tentrem”, Contemporary Javanese, Kawruh